Les implications morales de certaines dispositions législatives concernant l'avortement - Giroux, Michel (Les Cahiers de droit, 1982)
Abortion in Canada is mainly settled by S. 251 of the Canadian Criminal Code. The section states that abortion is a criminal act except when a therapeutic abortion committee for an approved hospital is of the opinion that the continuation of the pregnancy is or is likely to endanger the woman's life or health. As it now stands, the section is subject to considerable interpretation. Morals is one of the most fundamental aspects of abortion. Our legislation on the matter should reflect much aspect, first by "discriminatizing" abortion and, secondly, by recourse to social measures insuring the mother a real choice after proper consideration in ethics.